Assessing the impact of universities' entrepreneurial activity on regional competitiveness - Gonçalo Rodrigues Brás; Miguel Torres Preto; Ana Dias Daniel; Aurora Amélia Castro Teixeira (Administrative Sciences, 2023)
The aim of this study is to test the multidimensional construct of the Entrepreneurial University (EU), and therefore to confirm whether EU factors make a positive contribution to regional competitiveness. Data were collected from ten Portuguese Public Universities (PPUs) through a self-administered questionnaire. First- and second-order confirmatory factor analyses (CFA) were performed through factor and multiple linear regression analyses. The main findings show that EU related factors - perceived and combined with actual regional metrics - especially entrepreneurial supporting measures, positively contributed to regional competitiveness. This study shows policy makers that universities are not merely cost centres but provide knowledge spillovers that can have a positive influence on regional competitiveness.
Keywords: 350; entrepreneurial orientation; entrepreneurial university; higher education institutions; knowledge spillover; regional competitiveness